PhET Virtual Simulation Training to Improve the Competence of Elementary and Secondary School Teachers in Taniwel - Ashari B.P. Dulhasyim; Fryan Sopacua; Sally Untajana; Venty Sopacua (Pascasarjana Universitas Mataram, 2026)
This community service activity aims to equip teachers at SD Kristen Nikulukan Niwelehu, SD Negeri Sehati, and SMP Negeri 8 Taniwel to be able to implement PhET Simulation as an experimental-based learning media that is innovative and meets the needs of students. This program is designed to assist teachers in supporting learning related to experimental or practical activities for schools that do not have a Laboratory. In addition, it is important for a teacher to master and integrate technology-based learning media such as PhET simulations in the Science learning process. This mastery not only helps teachers deliver material in a more interesting and interactive way, but also encourages students to actively explore scientific concepts independently, making learning feel more engaging and meaningful. The service team organizes activities based on 4 stages, namely the preparation and briefing stage, implementation, and program sustainability. Community service activities received a positive response from partner parties, as evidenced by the responses from teachers, with teachers being very enthusiastic about participating in this activity (89%), and the presentation of the material and its application being felt very interesting to follow (86%), so that community service activities at SD Kristen Nikulukan Niwelehu, SD Negeri Sehati, and SMP Negeri 8 Taniwel can improve teacher competence in partner schools.